Corncob delignification through ultrasound - Venegas-Sánchez, Josué Addiel (2023)
In this research paper, the pretreatment with ultrasound of corncob for the removal of lignin was studied, which limits access to sugars within the lignocellulosic structure. The samples of corncob were obtained jointly from the International Maize and Wheat Improvement Center (CIMMYT). For the treatment, a 24 kHz ultrasonic device and a power of 100 W were used, likewise, it was exposed to different radiation times (30, 60, and 90 minutes) and different temperatures (40, 60, and 80 °C) in a solution adjusted to a concentration of 0.5% NaOH. The results showed that lignin can be separated in a specific way through treatment, having lignin removal yields of up to 8.6% with respect to the initial mass under treatment conditions of 60 °C for 1 hour. These results were supported by the SEM technique, which allowed us to observe the effect of the treatment, noticing an increase in the cavities of the lignocellulosic structure of the corncob. Therefore, pretreatment with ultrasound of corncob can be an option to obtain fermentable sugars and be included in a sustainable scheme for obtaining biofuels by decreasing the amount of NaOH in the pretreatment.